ISLAMIC PHILANTHROPY: POTENTIAL AND REALIZATION - Zuchroh, Imama (Proceeding International Seminar of Islamic Studies, 2023)
The work of Islamic philanthropy institutions in the country has benefited the community. From day to day, its contribution is increasingly evident. There are at least five areas of contribution of Islamic philanthropic organizations in Indonesia. First, in the field of da'wah. Second, in the field of education. Third, social humanitarianism. Fourth, the health sector. Meanwhile, the fifth area is the economic field. There are many models of productive zakat and waqf empowerment for community empowerment. However, it must be admitted that there is still a gap between potential and realization. There are at least four steps that must be taken to optimize the potential of ISF, First, it is necessary to conduct policy advocacy. Hopefully, existing policies can further support the development of Islamic philanthropy in Indonesia. Second, philanthropic institutions also need to strengthen the role of education and literacy. So that public awareness is formed. Third, collaborate between philanthropic institutions, both at home and abroad. Fourth, philanthropic institutions must continue to update the management model. continue to highlight their services through various means, such as e-commerce, e-wallets, and banking. This is an effort that must continue to be optimized in the digital era. The methodology used in this research is library research, various materials regarding ISF are collected and analyzed. So as to produce conclusions to optimize ISF so that it can become the mouth of various problems from inequality and poverty. So that realizing the prosperity of all Indonesian people is a necessity.